Efektivitas Aplikasi Pupuk Organik Cair Urine Sapi Terhadap Pertumbuhan Vegetatif Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pre Nursery - Manurung, Saroha; Aznur, Tifany Zia; Yosephine, Ingrid Ovie; Gamal, Syahrial (JURNAL AGROPLASMA, 2022)
This study was conducted to determine the effect of the application of liquid organic fertilizer in cow urine on the vegetative growth of oil palm seedlings in early nurseries. This research was conducted in the experimental garden of ITSI Medan. This research was conducted for 3 months. Starting from August 2021â€“October 2021. This study used a non-factorial Randomized Block Design (RAK) method consisting of 5treatments with 5 replications, so the number of samples was 25 seeds. Parameters observed were plant height, stem diameter, number of leaves, shoot dry weight, root dry weight, shoot wet weight and root wet weight. The data obtained were statistically analyzed by DMRT and ANOVA tests. The results of this study indicate that the application of liquid organic fertilizer cow urine has an effect on the vegetative growth of oil palm seedlings in early nurseries with the best dose of 20 ml cow urine. The standard gave some significant and very significant effects on stem height, stem diameter, number of leaves, but had no effect on wet weight and dry weight.Â Keywords:urine, pre nursery, poc